Assessment of Variation in Cryptolepis sanguinolenta (Lindl.) Schter., An Antimalaria Plant of The Family Periploceae Using Principal Component Analysis - AMEYAW, Y.; AKOTOYE, H.K.; PAPPOE, A.N.M.; OPOKU BOAHEN, Y.; EYIAH-BEDIAKO, F. (Asian Journal of Chemistry, 2010)
A survey research was conducted on Cryptolepis sanguinolenta (Lindl.) Schtr., an antimalarial plant harvested from three sampling sites, namely; Pepease, Mamfe and Abonse in the eastern region of Ghana. The aim was to determine whether there is an intraspecific relationship within the plant species, C. sanguinolenta using a secondary chemical constituent, that is; the total alkaloid content, morphological and anatomical characters. To this end, Principal Component Analysis (PCA) was applied to the data from the three sites to determine the existence of variations. The results showed the existence of variation and some of the variables were more influential or weighted more than others